DISIPLIN PERSPEKTIF DOLET UNARADJAN: SOLUSI ALTERNATIF DALAM MENGUBAH MINDSET DAN PERILAKU PROKRASTINASI AKADEMIK - Jihan Ramadhan; Maghfiroh Maghfiroh (Journal of Research and Thought on Islamic Education (JRTIE), 2020)
Abstract: This article examines the discipline offered by Dolet Unaradjan as a solution in improving the academic procrastination mindset and behavior. Where the mindset always leads to the individual's mindset that will produce a behavior in their daily life, the wrong mindset will give birth to the wrong behavior, and vice versa. Mindset often encourages individual human beings to behave according to the desired mindset. One of them is the academic procrastination behavior in individuals, this habit often occurs in every human being. Many studies and studies have discussed this behavior, in which almost every individual human being has this behavior, including us personally who often do the habit of procrastinating a job. This behavior is a symptom that exists in every human individual that starts from the wrong mindset, resulting in the academic procrastination behavior. This article uses library research, which is an effort to use library research to obtain data from library documents such as books, books, magazines, and other documents. Thus, the authors hope that the discipline of Dolet Unaradjan will give a good contribution in solving existing problems. The contribution that the authors have found by conducting a study of this article is that discipline is able to have a strong influence in improving and changing the individual's mindset which ultimately results in a good behavior and attitude, so that academic procrastination behavior can disappear by itself. Which of course is accompanied by personal maturity, be it intellectual, spiritual, and emotional maturity. Keywords: Discipline, Mindset, Academic Practice